Can we eliminate neoadjuvant chemoradiotherapy in favor of neoadjuvant multiagent chemotherapy for select stage II/III rectal adenocarcinomas: Analysis of the National Cancer Data base. Issue 5 (25th October 2016) - Cassidy, Richard J.; Liu, Yuan; Patel, Kirtesh; Zhong, Jim; Steuer, Conor E.; Kooby, David A.; Russell, Maria C.; Gillespie, Theresa W.; Landry, Jerome C.
Abstract : BACKGROUND: Stage II and III rectal cancers have been effectively treated with neoadjuvant chemoradiotherapy (NCRT) followed by definitive resection. Advancements in surgical technique and systemic therapy have prompted investigation of neoadjuvant multiagent chemotherapy (NMAC) regimens with the elimination of radiation (RT). The objective of the current study was to investigate factors that predict for the use of NCRT versus NMAC and compare outcomes using the National Cancer Data Base (NCDB) for select stage II and III rectal cancers. METHODS: In the NCDB, 21, 707 patients from 2004 through 2012 with clinical T2N1 (cT2N1), cT3N0, or cT3N1 rectal cancers were identified who had received NCRT or NMAC followed by low anterior resection. Kaplan‐Meier analyses, log‐rank tests, and Cox‐proportional hazards regression analyses were conducted along with propensity score matching analysis to reduce treatment selection bias. RESULTS: The 5‐year actuarial overall survival (OS) rate was 75% for patients who received NCRT versus 67.2% for those who received NMAC ( P < .01). On MVA, those who received NCRT had improved OS (hazard ratio, 0.77. P < .01), and this effect was confirmed on propensity score matching analysis (hazard ratio, 0.72; P = .01). In the same model, the following variables improved OS: age < 65 years, having private insurance, treatment at an academic center, living in an affluent zip code, a low comorbidity score, receipt of adjuvant chemotherapy, and a shorter interval before surgery (all P < .05). African Americans, men, patients with high‐grade tumors, those with cT3N1 tumors, and those who underwent incomplete (R1) resection had worse OS (all P < .05). CONCLUSIONS: In this series, the elimination of neoadjuvant RT for select patients with stage II and III rectal adenocarcinoma was associated with worse OS and should not be recommended outside of a clinical trial. Cancer 2017;123:783–93. © 2016 American Cancer Society . Abstract : Because the selective elimination of neoadjuvant radiation for stage II/III rectal adenocarcinomas is evolving, the National Cancer Data Base is used to identify US practice patterns, to determine predictors of receiving neoadjuvant multiagent chemotherapy versus traditional neoadjuvant chemoradiotherapy, and to identify factors associated with overall survival. The results indicate that eliminating radiation produces worse survival outcomes, and radiation should not be omitted outside of a clinical trial.